Going the distance: The pros and cons of expanding employees’ global knowledge reach - Morris, Shad S; Zhong, Bijuan; Makhija, Mona (Journal of International Business Studies, 2015)
While some scholars have suggested MNEs to be superior to markets for managing knowledge across geographically distant boundaries, how they actually accomplish this has not been fully considered. We address this void by developing and testing a model that highlights the critical role of organizational incentives in enhancing employees’ internal search and use of knowledge. Data from 166 knowledge-intensive projects support our argument that, in contrast to process-based incentives that influence more local search, outcome-based incentives motivate employee teams to reach well beyond their immediate location, which in turn enhances performance. At the same time, we demonstrate that expanded reach also increases the likelihood of accessing more codifiable knowledge, which can hurt performance. Our model examines the contradictory – and previously unknown – effects of global knowledge reach.